Curcumin-Containing Turmeric Dietary Supplement Clinical Trials: A Scoping Review. (7th June 2021) - Panknin, Timothy; Bucchireddigari, Bhanu; Howe, Carol; Hauer, Megan; Rossi, Anthony; Funk, Janet
Abstract: Objectives: Curcumin-containing, turmeric dietary supplements (CCDS) are one of the top selling botanicals in the United States. Medicinal turmeric has also been used for millennia in Ayurvedic medicine. However, questions about poor curcumin bioavailability and false readouts in some in vitro studies have led some researchers to question whether CCDS have medicinal effects in humans. A scoping review of the literature was therefore undertaken to identify clinical trials evaluating the efficacy of oral CCDS. Methods: Using a defined search strategy, eight databases were searched (thru 5/29/2019), identifying 4, 767 potential publications for inclusion, from which 315 remained after screening by three independent reviewers. These 315 were categorized by disease state and/or body system, following which data regarding study populations, design, and outcomes were extracted and analyzed. Results: The most commonly studied diseases in our identified CCDS trials were disorders of glucose and lipid metabolism ( n = 69), including type 2 diabetes mellitus ( n = 22); musculoskeletal disorders ( n = 50), of which osteoarthritis was the most studied ( n = 23); and gastrointestinal disorders ( n = 50), including non-alcoholic fatty liver disease ( n = 16). The majority of clinical trials, which varied in design quality, reported significant effects of CCDS on various objective (e.g., decreased cholesterol levels, increased adiponectin, improved glucose control) and/or subjective (e.g., reduced pain, improved quality of life in various populations) endpoints. While clinical outcomes varied with disease state, anti-inflammatory effects were a common clinical endpoint for which statistically significant effects were reported. Conclusions: Definitive conclusions on the clinical utility of CCDS for disease treatment are limited due to variable study methodology and quality, and lack of product uniformity. Despite these limitations, we found consistent indications among reviewed trials that CCDS are associated with beneficial outcomes (i.e., reduced inflammation, improved lipid profiles). Given the popularity of CCDS use in the United States, further large, well-designed human clinical trials exploring the benefits and safety of CCDS may be merited. Funding Sources: National Cancer Institute (NCI) NIH/NCI R01-CA174926.